No Way to Die. - Asong, Linus T. (Linus Tongwo), 1947-2012 (Langaa RPCIG, 2009)
What happens when a young man of talent and visions of greatness falls victim to a cruel set of circumstances over which he has no control? No Way to Die is such a story. Dennis Nunqam Ndendemajem gives up! Even when he is given a second chance to start again, he refuses to gather the broken pieces of his life together. He refuses to rebuild, and refuses to live. But he also finds no way to die.